Organizational Communication : A Case Study of a Large Urban Hospital - Jain, Harish (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1976)
The hospital study described here is one of a variety of organizational communication studies in several different countries and organizations as part of the International Communication Associations Communication Audit Project.